2014
DOI: 10.1016/j.jue.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

State incentives for innovation, star scientists and jobs: Evidence from biotech

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Each state-year dyad is a discrete observation for which the continuous dependent variable is regressed on the explanatory variables and controls. As in studies of state research and development tax credits (Wu, 2008) and biotechnology incentives (Moretti & Wilson, 2013), unit-level fixed effect regression models are customary for analyzing panels that exhaust the population and/or there is a need to control for unobserved unit heterogeneity.…”
Section: Methodology and Preliminary Diagnosticsmentioning
confidence: 99%
“…Each state-year dyad is a discrete observation for which the continuous dependent variable is regressed on the explanatory variables and controls. As in studies of state research and development tax credits (Wu, 2008) and biotechnology incentives (Moretti & Wilson, 2013), unit-level fixed effect regression models are customary for analyzing panels that exhaust the population and/or there is a need to control for unobserved unit heterogeneity.…”
Section: Methodology and Preliminary Diagnosticsmentioning
confidence: 99%
“…And if it is human capital that really drives growth, that can be subsidized directly. Moretti and Wilson (2014) find that taxbased incentives for R&D have a significant effect on luring biotech 'stars', with large multiplier effects in construction and retail jobs.…”
Section: Background: Public Support Of the Arts And Economic Developmentmentioning
confidence: 94%
“…Kleven, Landais, and Saez (2010) found evidence that top tax rates had strong mobility effects on elite European footballers and reported indications of sorting effects of highperformance players in low-tax countries. Moretti and Wilson (2014) explored the effect of tax policy on the migration of star scientists and found that state tax rates and credits induce movement among that population, with credits having a stronger ''pull effect'' (the policy in the destination state) and tax rates having a strong ''push effect'' (the policy in the state of origin).…”
Section: Taxationmentioning
confidence: 99%